White voices, black silences and invisibilities in the XIX century travel narratives (2015)
The manipulation of the image of Afro-descendants in XIX century travel narratives accounts for certain ideological practices. This essay does not only reflect on the representation of the Other. It also seeks to explore the ambivalence that occurs in the contact zones as well as discursive strategies used to depict Otherness. The recurrent portrayals of these populations turn out to be revealing because of all the ideas, attitudes and prejudice they convey. How do these rhetorical mechanisms come into play and what tensions do they inscribe? We will attempt to reflect on these issues through the exploration and comparison of travel accounts written by four travelers: Alexander Von Humboldt (1769-1859), Flora Tristán (1803-1844), Charles Darwin (1809-1882) and Miguel Cané (1851-1905). Keywords: Ambivalence, Travel literature, Post-colonialism, Identity, Representation, Race, Diaspora.